Weight status and hypertension among adolescent girls in Argentina and Norway: Data from the ENNyS and HUNT studies - Vik Torstein; Holmen Turid L; Cormick Gabriela; Gibbons Luz; Helsing Ragnhild M; Stray-Pedersen Marit; Belizán José M (BMC, 2009)
Abstract Background To provide data on overweight, obesity and hypertension among adolescent girls in Norway and Argentina. Methods Data was obtained from two population-based, cross-sectional and descriptive studies containing anthropometric and blood pressure measurements of 15 to 18 year old girls. The study included 2,156 adolescent girls from Norway evaluated between 1995 and 1997, and 669 from Argentina evaluated between 2004 and 2005. Results Around 15% of adolescent girls in Norway and 19% in Argentina are overweight or obese. Body mass index (BMI) distribution in these two countries is similar, with a low percentage (< 1%) of girls classified as thin. Norwegian adolescents show a height mean value 8 cm taller than the Argentinean. Obesity is strongly associated with systolic hypertension in both populations, with odds ratios of 11.4 [1.6; 82.0] and 28.3 [11.8; 67.7] in Argentina and Norway, respectively. No direct association between BMI and systolic hypertension was found, and only extreme BMI values (above 80th - 90th percentile) were associated with hypertension. Conclusion This study confirms a current world health problem by showing the high prevalence of obesity in adolescents and its association with hypertension in two different countries (one developed and one in transition).